Brisk walking and serum lipid and lipoprotein variables in previously sedentary women--effect of 12 weeks of regular brisk walking followed by 12 weeks of detraining. Issue 4 (December 1994) - Hardman, A E; Hudson, A
Abstract : The purpose of this study was to examine the effectiveness of brisk walking as a means of improving endurance fitness and influencing serum lipid and lipoprotein variables in previously sedentary women. Walkers (n = 10, mean (s.e.m.) age 47.3(2.0) years) followed a programme of brisk walking (mean(s.e.m.) speed 1.76(0.03) m s-1) for 12 weeks, after which the training stimulus was withdrawn. Controls (n = 10, mean(s.e.m.) age 41.6(1.2) years) maintained their habitual sedentary lifestyle throughout. Endurance fitness was determined using laboratory measures of responses to treadmill walking. Serum lipid and lipoprotein variables were determined in venous blood (12-h fasted). Body fatness was assessed by anthropometry and dietary practice using the 7-day weighed food intake technique. Measurements were repeated after 12 and 24 weeks. Brisk walking resulted in a decrease in heart rate and blood lactate concentration during exercise, while detraining was accompanied by a reversal of these changes. Changes in body mass and the ratio of circumferences at the waist and hip did not differ between groups but the sum of four skinfolds decreased with brisk walking and increased with detraining. High density lipoprotein (HDL) and HDL2 cholesterol increased with walking and decreased with detraining but no between group changes (analysis of variance, P < 0.05) were found in other lipid and lipoprotein variables. These findings suggest that regular brisk walking can improve endurance fitness and increase HDL cholesterol concentration in sedentary women.